Teenager’s food choice assessment: an empirical study on secondary school in Shah Alam / Amey Rozalina Azeman - Azeman, Amey Rozalina (2013)
Teenager is a basic term used to describe a group of people that age between 13 to 19 years old, who actively seeking their own ways and identity. During this age, their needs and wants may influence by internal and external factors. Their desire includes foods, fashionable clothes and much more. However, this present research is stressed on the way how teenagers choose foods to fulfilled their needs and want. Choosing healthy foods may regulate the body development and at the same time to increase physical and mental performance. The absence of disease such as overweight and eating disorder is a result of improper dietary pattern, terrible eating habit and inappropriate practicing of nutritional knowledge. This research topic is a building block of three independent variables, which is knowledge of foods, eating behavior and purchase power.5 hypotheses were developed based on the theoretical framework. The instrument used is closed ended questions of 5 point Likert scale and nominal scale for demographic information. To meet the requirement for this study, 425 sets of questionnaire in Bahasa Malaysia is randomly distributed to secondary school’s teenagers in Shah Alam (2 schools involve). However, only 360 set of completed response able to meet the study’s need. The data gathered is analyzed through descriptive statistic, reliability analysis, Pearson coefficient correlation and multiple regressions. From the analysis all 5 hypotheses is accepted. The finding shows that there is a positive relationship between knowledge of foods, eating behavior and purchase power towards food choice. In addition the most influential factor for teenagers in choosing food is eating behavior, whereas it’s accomplished the highest beta value (β=.424, p<.01) compared to other variables. In spite of this all the p-value is significant, which is less than 0.05. At the end of the study, several suggestions and implication are highlighted in order to show the contribution of this research area in different perspectives.